Lumpy Skin Disease: An insights in Pakistan - Muhammad Jamil, Noman Latif, Raheela Bano, Syed Akbar Ali, M. Ahsan Qaisar, Naimat Ullah, Muhammad Kashif, Mubarik Ali, Norina Jabeen, Ans Nadeem, Fateh Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Lumpy skin disease (LSD) is an enzootic infectious, seldom fatal and eruptive disease in Pakistan reported in 2022. It can result in variably high mortality and morbidity rates in animals characterized by nodules on their skin. LSD caused by Lumpy skin disease virus (LSDV), together with goatpox virus and sheeppox virus, belongs to genus Capripoxvirus and Poxviridae family. The disease affects a wide variety of domestic and wild animals, including buffaloes and cows. The main symptoms are high fever, nodular lesions on the skin, and mucous membranes of the respiratory and digestive tracts. The outbreak of lumpy skin disease caused severe economic losses among Pakistan’s animal keepers by reducing milk, beef production, causing sterility in males and abortions in females. Crossbreed and female cattle had significantly higher disease prevalence than their male counterparts. The introduction of new animals into farms was discovered to be one of the most significant risk factors in disease transmission. The aim of current review was to provide the information about LSDV because no study has conducted in Pakistan as it is new disease reported in 2022. The current review of literature will be useful to field veterinarians, herders, and animal health decision makers in Pakistan, as well as in taking appropriate measures to prevent future outbreaks of this disease. Keywords: Domestic animals; Cattle; Lumpy skin disease; Poxviridae; Pakistan